PENGARUH PRICE EARNING RATIO DAN RETURN ON ASSET TERHADAP PRICE TO BOOK VALUE - Maya Sari; J Jufrizen (KRISNA: Kumpulan Riset Akuntansi, 2019)
The purpose of this study was to determine whether there was an influence between Price Earning Ratio and Return On Assets on Price to Book Value on plantation companies listed on the Indonesia Stock Exchange (IDX) totaling 16 plantation companies, while samples that met the criteria in sampling for this study is a total of 8 plantation companies listed on the Indonesia Stock Exchange (IDX). The independent variable in this study consists of Price Earning Ratio and Return On Assets, while the dependent variable is Price to Book Value. This research approach uses an associative approach. The associative approach is an approach using two or more variables to determine the effect of one variable on another and data collection with documentation taken from the official website www.idx.co.id in the 2013-2016 period at Plantation companies listed on the Stock Exchange Indonesia. Samples were taken using purposive sampling method so that 8 companies were obtained as samples. Data analysis using multiple linear regression analysis, classical assumptions, hypothesis testing, and coefficient of determination with the help of SPSS 16 software. The results of this study indicate that Price Earning Ratio (PER) partially has no significant effect on Price to Book Value (PBV), Return On Asset (ROA) partially has a significant effect on Price to Book Value (PBV). And simultaneously states that Price Earning Ratio and Return On Assets have a significant effect on Price to Book Value on plantation companies listed on the Indonesia Stock Exchange.